The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018 IEEE 61st International Midwest Symposium on Circuits and Systems (MWSCAS) 2018
DOI: 10.1109/mwscas.2018.8624008
|View full text |Cite
|
Sign up to set email alerts
|

A Compact CMOS Memristor Emulator Circuit and its Applications

Abstract: Conceptual memristors have recently gathered wider interest due to their diverse application in non-von Neumann computing, machine learning, neuromorphic computing, and chaotic circuits. We introduce a compact CMOS circuit that emulates idealized memristor characteristics and can bridge the gap between concepts to chip-scale realization by transcending device challenges. The CMOS memristor circuit embodies a twoterminal variable resistor whose resistance is controlled by the voltage applied across its terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Memristor emulators can be divided into two types according to their structures: floating memristors [3][4][5][6][7][8][9][10][11][12][13] and grounded memristors [14][15][16][17][18][19][20][21][22][23][24], with only certain memristor emulator circuits being suitable for high frequencies in the order of megahertz (MHz) [4,5,7,10,16,17,23,24]. Some of them can operate with a variable configuration, as one of the solutions proposed here, meaning that it is possible to emulate grounded or floating type of memristor with the same circuits [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Memristor emulators can be divided into two types according to their structures: floating memristors [3][4][5][6][7][8][9][10][11][12][13] and grounded memristors [14][15][16][17][18][19][20][21][22][23][24], with only certain memristor emulator circuits being suitable for high frequencies in the order of megahertz (MHz) [4,5,7,10,16,17,23,24]. Some of them can operate with a variable configuration, as one of the solutions proposed here, meaning that it is possible to emulate grounded or floating type of memristor with the same circuits [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The author also introduced a first compact CMOS memristor emulator circuit [47,48] and the resulting dynamic synapse circuits [24] but concluded that non-volatile synapses are needed for long-term retention of weights, high synaptic density and low leakage power in trained neural networks. Consequently, the Neuromorphic computing architecture development requires synergistic development in devices, circuits and learning algorithms to take advantage of the high synaptic density while not being oblivious to the challenges at the device-circuit interface.…”
Section: Nanoscale Emerging Devicesmentioning
confidence: 99%
“…Furthermore, we recently showed, using a simple CMOS emulator circuit, that the pinched hysteresis characteristics of a conceptual memristor doesn't guarantee analog state retention [24,48]. Based on this discussion, we can assume the worst case scenario that many such RRAM devices in crossbar arrays, with or without setting compliance current, may end up as bistable nonvolatile memory cells.…”
Section: Challenges With Emerging Devices As Synapsesmentioning
confidence: 99%
“…The author also introduced a first compact CMOS memristor emulator circuit [26,27] and the resulting dynamic synapse circuits [28] but concluded that non-volatile synapses are needed for long-term retention of weights, high synaptic density, and low leakage power in trained neural networks. Consequently, the Neuromorphic computing architecture development requires synergistic development in devices, circuits and learning algorithms to take advantage of the high synaptic density while not being oblivious to the challenges at the device-circuit interface.…”
Section: Nanoscale Emerging Devicesmentioning
confidence: 99%
“…Furthermore, we we recently showed using a simple CMOS emulator circuit that the pinched hysteresis characteristics of a conceptual memristor doesn't guarantee analog retention [27,28]. Based on this discussion, we can assume the worst case scenario that many such RRAM devices in crossbar arrays, without setting compliance current, may end up as bistable nonvolatile memory cells.…”
Section: Challenges With Emerging Devices As Synapsesmentioning
confidence: 99%